2003
DOI: 10.1088/0953-2048/16/9/304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bending strain on the critical current of Bi-2223/Ag tapes with different structures

Abstract: We have evaluated the effect of bending strain on the critical current of Bi-2223/Ag tapes with different structures. The measured results were analysed using a symmetric pure bending model. The irreversible degradation indicates that the Ic reduction is caused mainly by crack formation and propagation in the brittle Bi-2223 ceramic core. Experimented results have shown that the number of filaments, as well as the structure of the tapes, could have strong effects on the measured apparent critical values of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…As the reported experimental observation in existing literature [9], an axial tensile strain causes a larger reduction in the critical current than a compressive strain. It may be motivated an effective method to reduce carrying-current degeneration by diminishing or avoiding tensile damage in superconducting filaments.…”
Section: Asymmetric Distribution Of Superconducting Coresupporting
confidence: 71%
See 2 more Smart Citations
“…As the reported experimental observation in existing literature [9], an axial tensile strain causes a larger reduction in the critical current than a compressive strain. It may be motivated an effective method to reduce carrying-current degeneration by diminishing or avoiding tensile damage in superconducting filaments.…”
Section: Asymmetric Distribution Of Superconducting Coresupporting
confidence: 71%
“…The micrographs showed that damage of filaments was not detected for the case of small deformation, while clear cracks were observed in the tensile side of the tape when the applied strain exceeds an irreversible strain. The further experimental observations [9] showed different locations of the multifilamentary Bi-2223/Ag tape during bending can cause different effects, and an improved bending strain tolerance was observed if the Bi-2223/Ag tape completely experiences a compressive stress state.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The conductor has a stainless-steel jacket outside the stabilizing copper to secure the mechanical rigidity and the jacket is welded at the joint. The strain is a problem also for HTS tapes [11][12][13], however, during the fabrication of the half-pitch segment of HTS conductors, YBCO tapes are imbedded into the jacket which is already bent and twisted in a helical shape, and thus, the YBCO tapes experience almost no strain during the conductor fabrication. Since the conductor assembly (by soldering) is done at ∼473 K, the difference of thermal contractions among composites of the conductor may give rise to some limited strains to YBCO tapes during the cooldown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that the critical current of Bi2223/Ag/Ag alloy composite tapes decreases with increasing applied tensile (e T ) and bending (e B ) strains beyond the irreversible strain due to the damage evolution of the Bi2223 filaments [1][2][3][4][5][6][7][8][9][10][11][12][13]. In the damage evolution process under the applied tensile strain, the residual strain e Bi,r of the filaments, which arises during cooling due to the difference in coefficient of thermal expansion among the Bi2223 filaments, Ag and Ag alloy [3,7,9,10,12] and tensile fracture strain e Bi,f of the filaments in the sample length direction (current transport direction) play a dominant role in the damage process.…”
Section: Introductionmentioning
confidence: 99%